PENGANTAR STUDI ISLAM: DEFINISI, TUJUAN, FUNGSI, DAN RUANG LINGKUP - Alvito, Muhammad; Rido, Muhammad; Harun, Basri; Ray Farris Midonsa; Kasful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic Studies in the contemporary era faces significant epistemological challenges, particularly the blurring boundaries between normative religious teachings and historical interpretations in the digital public sphere. This article aims to reconstruct and systematically map the fundamental foundations of Islamic Studies, including its definition, objectives, functions, and scope within a contemporary context. The study employed a qualitative approach using library research as the primary method. Data were collected through descriptive-analytical review of relevant primary and secondary literature published between 2020 and 2026, ensuring the relevance of findings to current developments. The results indicate that Islamic Studies has transformed from a monolithic and doctrinal approach into an interdisciplinary and multidimensional field. Conceptually, Islamic Studies is no longer limited to classical textual analysis but encompasses the interaction between revelation and social reality. The objectives of Islamic Studies have expanded from purely cognitive religious understanding to addressing global humanitarian issues such as religious moderation, digital ethics, and social justice. Functionally, Islamic Studies plays a role as an instrument of social transformation, digital literacy, and ethical guidance in responding to modern challenges. Its scope has also broadened to